2016
DOI: 10.1104/pp.16.00501
|View full text |Cite
|
Sign up to set email alerts
|

SHORT HYPOCOTYL 1 Encodes a SMARCA3-like Chromatin Remodeling Factor Regulating Elongation

Abstract: (Y.We.).In Arabidopsis (Arabidopsis thaliana), the UVR8-mediated signaling pathway is employed to attain UVB protection and acclimation to deal with low-dosage UVB (LDUVB)-induced stresses. Here, we identified SHORT HYPOCOTYL1 (SH1) in cucumber (Cucumis sativus), which regulates LDUVB-dependent hypocotyl elongation by modulating the UVR8 signaling pathway. We showed that hypocotyl elongation in cucumbers carrying the recessive sh1 allele was LDUVB insensitive and that Sh1 encoded a human SMARCA3-like chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 100 publications
(127 reference statements)
0
24
0
Order By: Relevance
“…Nucleotide diversity at the ll locus was investigated among 108 resequenced cucumber lines (Qi et al ., ) following Bo et al . (). The DNA‐binding residues in the LL protein were predicted with the DP‐Bind program (http://lcg.rit.albany.edu/dp-bind/).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Nucleotide diversity at the ll locus was investigated among 108 resequenced cucumber lines (Qi et al ., ) following Bo et al . (). The DNA‐binding residues in the LL protein were predicted with the DP‐Bind program (http://lcg.rit.albany.edu/dp-bind/).…”
Section: Methodsmentioning
confidence: 97%
“…We genotyped 12 cucumber lines with the ll-dCAPS2 marker inside the ll gene ( Figure S2) and found that all ll lines shared the ll allele at this marker locus. We examined the nucleotide variation at the LL locus among 108 resequenced lines, of which 11, 17 and 80 belonged to the wild, semi-wild and cultivated groups, respectively (Bo et al, 2016). Eleven single-nucleotide polymorphisms (SNPs) were identified within the CDSs; their positions and resulting amino acid substitutions among the three botanical varieties are presented in Table S2 and Figure S3, respectively.…”
Section: The W264 Residue In the Ll Protein Is Conserved In Natural Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the roles of the SWI/SNF chromatin-remodeling complex and CAF1 gene in plants. In Arabidopsis , a SMARCA3 -Like chromatin remodeling factor regulates low-dosage UVB-dependent hypocotyl elongation [ 11 ]. Loss-function of both AtCAF1a and AtCAF1b reduced expression of pathogenesis-related genes and was more susceptible to pathogen infection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flowering time and fruit size variation in the Xishuangbanna cucumber have also been studied, and a QTL analysis implicated 11 QTLs on two chromosomes in determining photoperiod-dependent flowering time and the round fruit shape ( Qu et al 2014 ; Pan et al 2017 ). The short hypocotyl is controlled by a recessive allele ( Bo et al 2016 ), and the carpel number of usually 5, not three carpels as in var. hardwickii and var.…”
Section: Discussionmentioning
confidence: 99%